Current Status of Educational Institutions - A Study (International Journal of Food and Nutritional Sciences, 2022)
In case of the Hon. Courts of India; it is said that they are good only for the Practicing Advocates and the Hon. Judges since they are not giving justice to the common litigants. Likewise; are the Educational Institutions catering to the needs of their stakeholders? This Research Question leads to several other sub-questions. Are the students getting the Qualitative Inputs; they need? Is the Teaching Fraternity getting the benefits; it deserves? Is the Non-Teaching Staff happy and satisfied? Does current education confer the benefits on the society; at large? Does the Industry get the candidate; it requires? Are the parents satisfied with the Gestation Period of Educational Courses; they are offering to their wards? Is the Government obtaining satisfactory returns from the learned students after investing valuable resources through educational institutions?